The impact of COVID-19 on palliative care social work: An online survey by a European Association of Palliative Care Task Force. (June 2023) - Roulston, Audrey; Ross, Jana; Dobrikova, Patricia; Piccione, Tania; Reigada, Carla; Mackova, Marie; Wasner, Maria
Background: The SARS-Cov-2 (COVID-19) pandemic affected the delivery of health and social care services globally. However, little is known about how palliative care social work services were impacted. Aim: The aim of this study was to capture and analyse data from palliative care social workers who provided professional support in a range of settings across 21 countries during the COVID-19 pandemic. Design: A cross-sectional survey-based design was used for this empirical study and this paper primarily focuses on the quantitative responses. Setting/participants: Participants, palliative care social workers, were drawn internationally via members of the EAPC Social Work Task Force and the World Hospice Palliative Care Social Work network. Results: We received 362 survey responses from 21 countries. Most (79%) respondents worked with adults in in-patient units or hospitals. The number of referrals during COVID-19 increased more in non-European countries, compared to European countries. The full range of social work services could no longer be delivered, existing services changed and 65.3% of participants reported higher levels of pressure during the pandemic, which was linked to higher levels of staff absence and additional duties. For many respondents (40.8%), this included facilitating online communication between patients and their families. Conclusions: Our findings indicate that restrictions to limit the spread of COVID-19 resulted in adaptations to service delivery, increased pressure on staff and moral distress, like other health and social care professions. All members of the palliative team need support and supervision to ensure effective interdisciplinary working and team cohesion.